Regulation by FSH of the dynamic expression of retinol-binding protein 4 in the mouse ovary - Yanwen Jiang; Yun Zhao; Shuxiong Chen; Lu Chen; Chunjin Li; Xu Zhou (BMC, 2018)
Abstract Background Ovarian retinoid homeostasis plays an important role in the physiological function of the ovary. Retinol-binding protein 4 (RBP4) acts as the mediator for the systemic and intercellular transport of retinol and is heavily involved in cellular retinol influx, efflux, and exchange. However, the expression patterns and regulatory mechanisms of Rbp4 in the ovary remain unclear. Methods The expression pattern of ovarian Rbp4 was examined in immature mice during different developmental stages and in adult mice during different stages of the estrous cycle. The potential regulation and mechanisms of ovarian Rbp4 expression by estrogen and related gonadotropins in mouse ovaries were also investigated. Results The present study demonstrated that the ovarian expression of Rbp4 remained constant before puberty and increased significantly in the peripubertal period. In adult female mice, the expression of Rbp4 increased at proestrus and peaked at estrus at both the mRNA and protein levels. The protein distribution of RBP4 was mainly localized in the granulosa cell and theca cell layer in follicles. In addition, the expression of Rbp4 was significantly induced by follicle-stimulating hormone (FSH) or FSH + luteinizing hormone (LH) in combination in immature mouse (3 weeks old) ovaries in vivo and in granulosa cells cultured in vitro, both at the mRNA and protein levels. In contrast, treatment with LH or 17β-estradiol did not exhibit any observable effects on ovarian Rbp4 expression. Transcription factors high-mobility group AT-hook 1 (HMGA1), steroidogenic factor 1 (SF-1), and liver receptor homolog 1 (LRH-1) (which have been previously shown to be involved in activation of Rbp4 transcription), also responded to FSH stimulation. In addition, H-89, an inhibitor of protein kinase A (PKA), and the depletion of HMGA1, SF-1, and LRH-1 by small interfering RNAs (siRNAs), resulted in a dramatic loss of the induction of Rbp4 expression by FSH at both the mRNA and protein levels. Conclusions These data indicate that the dynamic expression of Rbp4 is mainly regulated by FSH through the cAMP-PKA pathway, involving transcriptional factors HMGA1, SF-1, and LRH-1, in the mouse ovary during different stages of development and the estrous cycle.